IMPLEMENTASI PROGRAM PENCEGAHAN HUMAN IMMUNODEFICIENCYVIRUS/AQCQUIRRED IMMUNODEFICIENCY SYNDROME (HIV/AIDS) PADA PUSKESMAS PARINGIN SELATAN KABUPATEN BALANGAN - Budiman, Arif; Maulida, Lusi (SINERGI : Jurnal Riset Ilmiah, 2025)
To prevent and overcome HIV/AIDS cases in Balangan Regency,the implementation of prevention programs at the South Paringin Health Center still faces several challenges.Community stigma and discrimination against this disease are still high, and the lack of infrastructure such as leaflet counseling media is an obstacle. This study used qualitative descriptive method involving 14 respondents.Data were collected through interviews, observation, and documentation, and analyzed using a variety of analytical techniques.The results showed that the HIV/AIDS prevention program at Puskesmas Paringin Selatan was effective, but there was still a lack of resources and communication. Factors supporting program implementation include policy stakeholder commitment, cross-program and cross-sector involvement, and community participation. However, stigma and societal discrimination are inhibiting factors. To improve program implementation, it is recommended that the Health Office and Puskesmas program managers strengthen information about HIV/AIDS, at-risk groups conduct routine screening,and communities participate in the planning and implementation of this prevention program.